2018
DOI: 10.1186/s13550-018-0357-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of simultaneous 18F-FDG PET/MRI using a combination of metabolo-volumetric parameters and apparent diffusion coefficient in treated head and neck cancer

Abstract: BackgroundThe aim of this study was to determine the usefulness of combined positron emission tomography (PET)/magnetic resonance imaging (MRI) parameters provided by simultaneous 18F-fluorodeoxyglucose (FDG) PET/MRI for the prediction of treatment failure in surgically resected head and neck cancer. We hypothesized that PET parameters corrected by tumor cellularity (combined PET/MRI parameters) could predict the prognosis. On regional PET, maximum standardized uptake value (SUVmax) was measured as metabolic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 35 publications
2
30
1
Order By: Relevance
“…In every case, the following combined PET/ADC parameters were calculated according to previous descriptions [17] , [19] : SUV max divided by ADC min (SUV max /ADC min ), SUV max divided by ADC men (SUV max /ADC mean ), TLG divided by ADC min (TLG/ADC min ), TLG divided by ADC mean (TLG/ADC min ), MTV divided by ADC min (SUV max /ADC min ), MTV divided by ADC mean (SUV max /ADC mean ). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In every case, the following combined PET/ADC parameters were calculated according to previous descriptions [17] , [19] : SUV max divided by ADC min (SUV max /ADC min ), SUV max divided by ADC men (SUV max /ADC mean ), TLG divided by ADC min (TLG/ADC min ), TLG divided by ADC mean (TLG/ADC min ), MTV divided by ADC min (SUV max /ADC min ), MTV divided by ADC mean (SUV max /ADC mean ). …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, some authors suggested that several 18 F-FDG-PET, DWI and DCE MRI parameters can be combined together [17] , [18] , [19] . For example, Baba et al calculated a new parameter, namely SUV/ADC, and showed that it had a great potential in differentiation between malignant and benign breast lesions [17] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited data on the combination of imaging techniques was published. Kim et al [46] found that volumetric MATV, TLG corrected by tumor cellularity (ADC min and ADC mean ) and were prognostic for LR [46]. However, their patient population underwent surgery, and sub-optimal delineation of only one imaging technique was performed.…”
Section: Tablementioning
confidence: 99%
“…There is a limited number of studies on the relationship between PET imaging and HPV status in HNSCC [3,[15][16][17]. Furthermore, very few studies concern the utility of PET/MRI in the characterization of HPV-related HNC [8,18]. According to our knowledge, there are no literature reports documenting the correlation between Epstein-Barr virus (EBV) status and PET/MRI features.…”
Section: Introductionmentioning
confidence: 99%